Bringing Buddhism to Tibet. History and Narrative in the DBA' BZHED Manuscript - Doney, Lewis (Beyond Boundaries, 2021)
Bringing Buddhism to Tibet is a landmark study of the Dba' bzhed-a seminal history recounting the introduction of Buddhism to Tibet. Preserved in a single copy, the Dba' bzhed stands at the head of a long tradition of history writing in the Tibetan language. This book gives the first full transcription and facing translation of the Dba' bzhed, coupled with a detailed analysis by leading scholars of the text and its context and narrative structure.